Enhancing Educational Impact: Exploring Effective Media And Public Relations Techniques In Educational Institutions - Maulidia, Maulidia; Sanjani, M. Aqil Fahmi (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2023)
Abstract. This study aims to analyze the role of the media and public relations techniques in the context of educational institutions. Educational institutions have a big responsibility to convey information to the public, both through print media and through direct communication with stakeholders. So that the media and public relations techniques play a very important role in building a positive image of educational institutions and maintaining good relations with the public. This research uses secondary data obtained through literature studies, scientific journals, books, articles, and other sources of information related to media topics and public relations techniques in educational institutions. The data is analyzed systematically and critically to gain an in-depth understanding of the concepts, theories and practices related to the use of media and public relations techniques in an educational context. The results of this study indicate that the media and public relations techniques play an important role in building a positive image of educational institutions, increasing stakeholder engagement, and increasing effective communication between educational institutions and the community. The use of public media such as newspapers, television, radio, and social media has opened new opportunities for educational institutions to convey information widely and quickly to the public. Public relations techniques such as press conferences, promotional activities, and direct interaction with the community are also an important part of the educational institution's communication strategy. The role of media in public relations in educational institutions is very important and diverse. Educational institutions rely on media to reach a wider audience, including students, parents, prospective students, alumni, donors, policymakers and the general public.